2017
DOI: 10.5334/gjgl.27
|View full text |Cite
|
Sign up to set email alerts
|

Bias in polar questions: Evidence from English and German production experiments

Abstract: Different polar question forms (e.g., Do you / Do you not / Don't you / Really? Do you... have a car?) are not equally appropriate in all situations. The present experiments investigate which combinations of original speaker belief and contextual evidence influence the choice of question type in English and German. Our results show that both kinds of bias interact: in both languages, positive polar questions are typically selected when there is no original speaker belief and positive or non-informative context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 9 publications
8
55
1
Order By: Relevance
“…Although to our knowledge it has not previously been tested whether prosody marks the checked proposition of English HiNQs, an observation by Domaneschi et al (2017) hints that this may be the case. They showed that in a context in which a speaker with an existing bias for p encountered evidence that their addressee believed ¬ p (as in (1) above), when German participants selected HiNQs in the experiment they uniformly realized them with a nuclear pitch rise, whereas British English participants sometimes used rises and sometimes falls.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although to our knowledge it has not previously been tested whether prosody marks the checked proposition of English HiNQs, an observation by Domaneschi et al (2017) hints that this may be the case. They showed that in a context in which a speaker with an existing bias for p encountered evidence that their addressee believed ¬ p (as in (1) above), when German participants selected HiNQs in the experiment they uniformly realized them with a nuclear pitch rise, whereas British English participants sometimes used rises and sometimes falls.…”
Section: Introductionmentioning
confidence: 88%
“…Instead, the felicity of their use depends both on the speaker’s prior beliefs regarding the checked proposition p and the new evidence provided by the conversational context. For example, Domaneschi, Romero, and Braun (2017) manipulated the original speaker bias – see (1a) with speaker bias for the proposition p – and contextual evidence – see (1b) with evidence for ¬ p . They found that in such situations with conflicting biases, English participants most often chose negative polar questions with negation in a high position, as in (1c); by contrast, positive polar questions as in (1d) were almost never uttered by participants as a response in the same context and thus seem inappropriate (see Domaneschi et al, 2017, for empirical results on these and other combinations of biases).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 At no point was gender found to be a significant factor for any of the contexts, and so this was removed from the models. 7 Evidential context has been shown to affect speakers' choice of question form (Domaneschi, Romero, & Braun 2017). I leave evidence as a variable in the models presented here where relevant, but do not discuss the effects; see Jamieson (2018) for details.…”
Section: (20)mentioning
confidence: 99%
“…It is felicitous in different kinds of contexts, i.e. it has a different bias profile from a NPQ with high negation (see Domaneschi, Romero & Braun 2017 for a discussion of German NPQs). We suggest that the NRQs in (30a.i&ii) differ from each other in a similar way.…”
Section: Polarity-sensitive Items In Rejecting Questions: Evidence Fomentioning
confidence: 99%